The use of multicomponent ear drops in the treatment of otitis of various etiologies in animals - Arisov, Mikhail Vladimirovich; Indyuhova, Evgenia Nikolaevna; Arisova, Gulnara Bakitovna (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of this study was to investigate the efficacy of newly developed multicomponent ear drops for the treatment of otitis caused by parasites, bacteria, and fungi in dogs, cats, ferrets, fancy rabbits, and foxes. Materials and Methods: A new drug for veterinary use was developed that contained levofloxacin hemihydrate (0.3%), clotrimazole (0.1%), dexamethasone sodium phosphate (0.1%), and moxidectin (0.01%). In the initial stage of otoacariasis (or the ear form of psoroptic scab), the drug was used twice with an interval of 5–7 days. When otoacariasis (psoroptic scab) was complicated by otitis of bacterial and/or fungal etiology, the drug was used as follows: instilled once a day, within 10–14 days in the ear canal for 2–5 drops of the drug. The study of therapeutic efficacy was performed on cats, dogs, ferrets, foxes, and fancy rabbits with ear pathology. Results: The recovery of cats, ferrets, dogs, and foxes after the double use of ear drops during otoacariasis was established. In the ear form of psoroptic scab in fancy rabbits after treatment, Psoroptes cuniculi mites were not detected. The specific (antimicrobial and antifungal) activity of the drug was confirmed in vivo using the following scheme of drug use: the drug was instilled once a day, within 10–14 days in the ear canal, 2–5 drops of the drug in animals with external otitis and otitis media. Conclusion: The rational combination of active components developed in this study is effective and safe for use in animals with microbial diseases of the ears. J. Adv. Vet. Anim. Res., 7(1): 115-126, March 2020